2012
DOI: 10.1111/j.1949-8594.2011.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Voices from the Front Lines: Exemplary Science Teachers on Education Reform

Abstract: The purpose of this study is to gain insight into the experiences that nationally award‐winning, exemplary science teachers have had over their career and examine the alignment of their responses with calls for K‐12 science education reform from a selection of prominent commissioned government reports since 1980. From an assessment of the alignment of exemplary teachers, calls for reform have had a limited effect and highlight the weakness of using national reports as a wide‐scale, nationalized approach to sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Although the literature is limited in regard to the barriers to implementing engineering in the elementary classroom, the research community is better informed about the barriers to implementing science in the elementary curriculum. Studies aimed at describing the barriers to implementing inquiry science at the elementary level report barriers that cut across contexts (e.g., school location, grade level taught, years of teaching experience) and include a lack of content knowledge (Burton & Frazier, ; Sexton, Atkinson, & Goodson, ); inadequate preservice training (Blanchard, Osborne, Wallwork, & Harris, ); and a lack of resources, planning time, and instructional time (often due to a focus on tested subjects) (Blanchard et al, ; Cartwright, ; Santau & Ritter, ). Further, based on survey responses from 977 K‐12 teachers in North Carolina, Blanchard et al () reported teacher comfort related to inquiry teaching methods was the most significant variable in determining whether teachers would teach using inquiry.…”
Section: Related Literaturementioning
confidence: 99%
“…Although the literature is limited in regard to the barriers to implementing engineering in the elementary classroom, the research community is better informed about the barriers to implementing science in the elementary curriculum. Studies aimed at describing the barriers to implementing inquiry science at the elementary level report barriers that cut across contexts (e.g., school location, grade level taught, years of teaching experience) and include a lack of content knowledge (Burton & Frazier, ; Sexton, Atkinson, & Goodson, ); inadequate preservice training (Blanchard, Osborne, Wallwork, & Harris, ); and a lack of resources, planning time, and instructional time (often due to a focus on tested subjects) (Blanchard et al, ; Cartwright, ; Santau & Ritter, ). Further, based on survey responses from 977 K‐12 teachers in North Carolina, Blanchard et al () reported teacher comfort related to inquiry teaching methods was the most significant variable in determining whether teachers would teach using inquiry.…”
Section: Related Literaturementioning
confidence: 99%
“…Because engineering is included within NGSS, the barriers to teaching science may provide insight into possible barriers to teaching engineering. When describing the barriers to implementing inquiry science at the elementary level, many teachers list lack of content knowledge [7], [8]; inadequate pre-service training [9]; and a lack of resources, planning time, and instructional time (often due to a focus on tested subject matter) as inhibiting factors [9] - [10]. Further, Blanchard et al [9] reported that teacher comfort related to the inquiry teaching methods was the most significant variable in determining whether teachers would teach using inquiry [9].…”
Section: Related Literaturementioning
confidence: 99%
“…Further, Blanchard et al [9] reported that teacher comfort related to the inquiry teaching methods was the most significant variable in determining whether teachers would teach using inquiry [9]. In fact, when interviewing award winning science teachers from grades K-12, Burton and Frazier [7] reported that all respondents said elementary teachers lacked the content and pedagogical knowledge required to teach inquiry and many were intimidated by inquiry and avoided teaching with it.…”
Section: Related Literaturementioning
confidence: 99%
“…Recent research in science education has demonstrated that effective PD has a direct impact on teachers' development as well students' development (e.g., [7][8][9]). ese studies also show that teachers who, in particular, participated in inquirybased PD programs have been shown to effectively increase the quality of their science instruction by implementing practices in ways that are similar to strategies used by scientists in their own research (e.g., asking research questions, formulating hypothesis, conducting repeated observations, and making predictions).…”
Section: Introductionmentioning
confidence: 99%